Stem cell therapy: curcumin does the trick - Sharifi, Simin; Vahed, Sepideh Zununi; Ahmadian, Elham; Dizaj, Solmaz Maleki; Abedi, Atefeh; Khatibi, Seyed Mahdi Hosseiniyan; Samiei, Mohammad (Wiley, 2019)
Curcumin is a dietary polyphenol and a bioactive phytochemical agent that possesses anti-inflammatory, antioxidant, anticancer, and chemopreventive properties. Some of the predominant activities of stem cells include regeneration of identical cells and the ability to maintain the proliferation and multipotentiality. However, these cells could be stimulated to differentiate into specific cell types. Curcumin protects some stem cells from toxicity and can stimulate proliferation and differentiation of stem cells. In the present review, we summarize the antioxidant, stemness activity, antiaging, and neuroprotective as well as wound healing and regenerative effects of curcumin